NIKAH SIRRI: SUB ORDINASI PEREMPUAN BERBUNGKUS HUKUM - Heri Junaidi (An Nisa'a, 2012)
The difference of individual or group of people pursuant of "behavior", entangling numbers of problems which deal with woman value in society and woman value as an individual. Though al-Qu’ran differentiate pursuant to pious charitable, al-Qur'an do not build peripheral assess for certain behavior. This matter makes every social system determine different value behavior. Every ordinary social system conduct and every society have made difference between scope of woman clan and men folk. Its problem is depending on tradition that man used to be looked more valuable than woman. How unfair that viewpoint division.  Unregistered married looked as one of subordination style woman in togetherness value point of view. This article will study farther about unregistered married from side of subordinating woman.